gC1qR: A New Target for Cancer Immunotherapy - Lei, Yanna; Li, Xiaoyu; Qin, Diyuan; Zhang, Yugu; Wang, Yongsheng (Frontiers in Immunology, 2023)
Although breakthroughs in cancer treatment have been achieved, immunotherapy yields only modest benefits in most patients. There is still a gap in clarifying the immune evasiveness and immune-resistance mechanisms. Identifying other candidate targets for cancer immunotherapy is therefore a clear unmet clinical need. The complement system, a pillar of innate immunity, has recently entered the limelight due to its immunoregulatory functions in the tumor microenvironment (TME). In particular, gC1qR, a receptor for globular heads of C1q, serves as a promising new target and has attracted more attention. gC1qR, also named P32/C1qBP/HABP1, is a multifunctional protein that is overexpressed in various cancers and holds prognostic value. It regulates the tumorigenic, progression and metastatic properties of tumor cells through several downstream signaling pathways, including the Wnt/β-catenin, PKC–NF-κB and Akt/PKB pathways. A few preclinical experiments conducted through gC1qR interventions, such as monoclonal antibody, chimeric antigen receptor T‐cell (CAR‐T) therapy, and tumor vaccination, have shown encouraging results in anticancer activity. The efficacy may rely on the regulatory role on the TME, induction of tumor cells apoptosis and antiangiogenic activity. Nevertheless, the current understanding of the relationship between cancer immunotherapy and gC1qR remains elusive and often contradictory, posing both opportunities and challenges for therapeutic translation in the clinic. In this review, we focus on the current understanding of gC1qR function in cancer immunology and highlight the vital roles in regulating the TME. It also examines the rationale behind targeting gC1qR and discusses the potential for translating into clinical practice.